Black liquor gasification - Bajpai, P. (Pratima) (Elsevier, 2014)
"Black Liquor Gasification (BLG) is a first of its kind to guide chemical engineers, students, operators of paper plants, technocrats, and entrepreneurs on practical guidelines and a holistic techno-enviro-economic perspective applicable to their future or existing projects based on the treatment of black liquor for energy production. BLG describes the gasification process as a more efficient alternative to current processes for the conversion of black liquor biomass into energy. BLG operates largely in sync with other methods to improve pulp-making efficiency. This book explains how BLG offers a way to generate electricity and to reclaim pulping chemicals from black liquor, and why BLG would replace the Tomlinson recovery boiler for the recovery of spent chemicals and energy. Describes the utilization of black liquor as a source of energy Provides a detailed account of black liquor gasification processes for the production of energy and chemicals from black liquor Provides guidelines to chemical engineers for the treatment of black liquor."